Single-Cell RNA Sequencing of Peripheral Blood Mononuclear Cells From Acute Myocardial Infarction - Qian, Jun; Gao, Yanhua; Lai, Yan; Ye, Zi; Yao, Yian; Ding, Keke; Tong, Jing; Lin, Hao; Zhu, Guoqi; Yu, Yunan; Ding, Haoran; Yuan, Deqiang; et al. (Frontiers in Immunology, 2022)
Background: Acute myocardial infarction (AMI) can occur in patients with atherosclerotic disease, with or without plaque rupture. Previous studies have indicated a set of immune responses to plaque rupture. However, which specific circulating immune cell subsets mediate inflammatory in plaque rupture remain elusive. Methods: Ten AMI patients were enrolled in our study (five with and five without plaque rupture; plaque characteristics identified by optical coherence tomography). We analyzed the transcriptomic profile of peripheral blood mononuclear cells by single-cell RNA sequencing. Results: We identified 27 cell clusters among 82,550 cells, including monocytes, T cells, NK cells, B cells, megakaryocytes, and CD34+ cells. Classical and non-classical monocytes constitute the major inflammatory cell types and pro-inflammatory genes such as CCL5, TLR7, and CX3CR1 were significantly up-regulated in patients with plaque rupture. Whereas the neutrophil activation and degranulation genes as FPR2, MMP9, and CLEC4D were significantly expressed in the intermediate monocytes derived from patients without plaque rupture. We also found that CD4+ effector T cells may contribute to plaque rupture by producing a range of cytokines and inflammatory-related chemokines, while CD8+ effector T cells expressed more effector molecule in patients without plaque rupture as GZMB, GNLY, and PRF1, which may contribute to the progress of plaque erosion. Additionally, NK and B cells played a significant role in activating inflammatory cells and promoting chemokine production in plaque rupture. Cell-cell communication elaborated characteristics in signaling pathways dominated by inflammatory activation of classical monocytes in patients with plaque rupture. Conclusions: Our studies demonstrate that the circulating immune cells of patients with plaque rupture exhibit highly pro-inflammatory characteristics, while plaque erosion mainly presented with intermediate monocytes amplification, neutrophil activation and degranulation. These findings may provide novel targets for precise treatment of patients with AMI.